ANÁLISIS E INTERPRETACIÓN A LOS ESTADOS FINANCIEROS DE LA ESTACIÓN DE SERVICIOS DE LA COOPERATIVA DE TRANSPORTES LOJA, DE LA CIUDAD DE LOJA, PERIODOS 2015- 2016 - Morocho Montaño, María Guadalupe (2019)
This thesis work entitled "Analysis and Interpretation to the Financial Statements of the Service Station of the Loja Transport Cooperative, of the City of Loja, 2015-2016 Periods.", Was carried out in order to comply with the requirement prior to obtaining the Degree in Accounting Engineering and Auditing Public Accountant - Auditor, at the National University of Loja. In addition, it allows compliance with the proposed objectives to make reference to: Establish the financial structure to know the different items that intervene in the economic-financial position of the Station, which allowed to know the composition of the liability plus equity, which is represented by a total of $ 1,149,689.60; corresponds to the liability $ 519,190.55; and to Equity a value of $ 630,499.05 belonging to the last period analyzed, showing that the company reflects a low level of short and long-term debt, and has its own capital to finance its activities. Apply methods of vertical and horizontal analysis in order to know the variations suffered by the accounts and items from one period to another; as a result, the other accounts and receivables of 2016 generated a decrease of -93.11% and therefore the account of the bank and other institutions accounts increased by 3144.11%; which is convenient for the 5 company; since, it achieved with the purpose of portfolio recovery; however, there are considerable amounts in its non-current liabilities, deducting that the company did not fully recover its credits, but rather readjusted them in other current liabilities. Likewise, financial indicators were used to verify the financial situation of the company, demonstrating that the Service Station has a significant turnover of the merchandise available for sale due to the size of the company and the demand of customers, in 2015 saw a turnaround in its inventories of 69.72 times, while for the year 2016 an increase of 69.95 times occurred, this shows that despite the competition, sales in both periods have reached representative levels; which is extremely positive, since it generates satisfaction in the administration and maximizes the value of the company and therefore the profits. Finally, a report was drawn up containing conclusions and recommendations that will help the manager to make timely decisions, thereby demonstrating that the Service Station maintains a liquidity of $ 1.99, the acid test of $ 1.89 for 2016, thus counting immediate liquidity in such a way that the company could have easily faced its short and long-term obligations.